ARBITRATION TRENDS IN CENTRAL ASIAN JURISDICTIONS (World Bulletin of Management and Law, 2024)
Arbitration serves as a critical mechanism for resolving disputes in a globalized economy, offering flexibility, neutrality, and enforceability. In Central Asia, the development of arbitration frameworks has become increasingly significant for fostering economic growth, attracting foreign investment, and enhancing legal infrastructure. This article provides a comprehensive analysis of arbitration trends in Central Asian jurisdictions, examining the historical context, legal framework, establishment of arbitration institutions, role in economic development, challenges, strategies for enhancement, comparative analysis, and future prospects